2009
DOI: 10.1088/0957-4484/20/42/425202
|View full text |Cite
|
Sign up to set email alerts
|

White-light electroluminescence from ZnO nanorods/polyfluorene by solution-based growth

Abstract: We report bright white-light electroluminescence (EL) from a diode structure consisting of a ZnO nanorod (NR) and a p-type conducting polymer of poly(fluorine) (PF) fabricated using a hydrothermal method. ZnO NRs are successfully grown on an organic layer of PF using a modified seeding layer. The EL spectrum shows a broad emission band covering the entire visible range from 400 to 800 nm. White-light emission is possible because the ZnO-defect-related emission from the ZnO NR/PF heterostructure is enhanced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Finally, we note the differences in electroluminescence of the Device B architecture (figure 4d) compared with that reported elsewhere for ZnO NRA HyLEDs, most notably the lack of an emission peak at ~380 nm associated with ZnO band-edge emission [29,30,48] . In NRA based devices this is usually the most intense emission peak with weak contributions, attributed to emission from defect states, also reported in the 500-600 nm range.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…Finally, we note the differences in electroluminescence of the Device B architecture (figure 4d) compared with that reported elsewhere for ZnO NRA HyLEDs, most notably the lack of an emission peak at ~380 nm associated with ZnO band-edge emission [29,30,48] . In NRA based devices this is usually the most intense emission peak with weak contributions, attributed to emission from defect states, also reported in the 500-600 nm range.…”
Section: Resultsmentioning
confidence: 46%
“…For example Yang et al only recently first reported efficiencies for a UVemitting diode based on a ZnO NRA/poly(3,4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS) structure [27] -almost a decade after Könenkamp et al first reported UV emission from a diode based on the same materials [28] . Reports of visible light emission from devices of ZnO NRAs and light-emitting polymers such as polyfluorene (PFO) [29] or poly(2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene) (MEH-PPV) [30] , are given by only electroluminescent (EL) emission spectra [31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the ZnO NR surfaces and the PFO thin films makes the PFO link up with the ZnO, which in turn leads to ZnO NR/PFO interfaces containing strong defect emissions. 24 The PFO defect emission is attributed to the formation of on-chain defects in the presence of oxygen or fluorenone. 25 The fluorenone defects are generated through the incorporation of oxygen as O¼C bonds in the polymer backbone, which can easily be formed by electro-(or photo-) oxidation of the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…26 This is ascribed to the fact that the electron mobility in ZnO NRs is higher than the hole mobility in PFO. 24 Electrons at high injection currents directly traverse at the PFO/ZnO interface and because the PFO layer is sufficiently thin (29.1 nm), the probability of an electron recombining with a hole at the PFO side becomes a minimum. This will favor an accumulation of electrons at the PFO/PEDOT:PSS interface, which may shift the recombination zone towards this interface.…”
Section: -5mentioning
confidence: 99%
“…14 Combining both polymers and n-type ZnO nanorods in hybrid-configuration LEDs is a novel method that makes use of the advantageous properties of both materials to provide LEDs with wide emission range. Fabrication of ZnO nanorods and polymer p-n junctions, 15 which provides an approach for the balance of the hole and electron mobility to construct high-performance LEDs, is necessary to realize practical LED applications. 16 In the current study, we designed LED based on 1D ZnO nanorods and poly(2-methoxy,5-octoxy)-1,4-phenylenevinylene (MOPPV).…”
Section: Introductionmentioning
confidence: 99%